2019
DOI: 10.1002/adbi.201900104
|View full text |Cite
|
Sign up to set email alerts
|

A Human Liver‐on‐a‐Chip Platform for Modeling Nonalcoholic Fatty Liver Disease

Abstract: The liver possesses a unique microenvironment with a complex internal vascular system and cell–cell interactions. Nonalcoholic fatty liver disease (NAFLD) is the most common form of chronic liver disease, and although much effort has been dedicated to building models to target NAFLD, most in vitro systems rely on simple models failing to recapitulate complex liver functions. Here, an in vitro system is presented to study NAFLD (steatosis) by coculturing human hepatocellular carcinoma (HepG2) cells and umbilica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 38 publications
3
64
0
Order By: Relevance
“…After overnight incubation, the steatosis inducing diet was given for 8 days, and the media was refreshed and collected every 2 days. In line with our previous report and other studies, spheroids supplemented with FFAs showed higher levels of lipid accumulation over 8 days compared to those cultured with healthy diet (Figure D,E), indicating the proposed system could provide an ideal model for the study on the progress of the disease from NAFL to NASH.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…After overnight incubation, the steatosis inducing diet was given for 8 days, and the media was refreshed and collected every 2 days. In line with our previous report and other studies, spheroids supplemented with FFAs showed higher levels of lipid accumulation over 8 days compared to those cultured with healthy diet (Figure D,E), indicating the proposed system could provide an ideal model for the study on the progress of the disease from NAFL to NASH.…”
Section: Resultssupporting
confidence: 92%
“…Here, different cell types, human hepatocytes (HepG2 or HepaRG), HUVECs, and HKCs, were mixed in appropriate ratios to generate the multicellular spheroids in the chip system. The spheroid size (200 cells per spheroid), that was previously optimized by controlling the seeding density, was chosen due to the absence of a necrotic core as well as good circularity and low aspect ratio which are necessary to sustain proper oxygen tension in the spheroid. The chip system is based on an array of interconnected honeycomb structures which have a similar size to the liver lobules, which are the functional units of the liver, and allow for molecular communications between the spheroids, mimicking the in vivo environment of the liver physiology.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations